PEMBELAJARAN BERBASIS MEDIA GAME EDUKASI DALAM MEMOTIVASI SISWA BELAJAR PENDIDIKAN PANCASILA KELAS V DI SEKOLAH DASAR NEGERI 4 NYALIAN KABUPATEN KLUNGKUNG - Dearadini, Ketut Yumanda; Kusuma, I Made Wirahadi; Suryawan, I Gde (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning motivation is one of the key factors influencing the success of the learning process. However, the implementation of Pancasila Education in elementary schools still faces several challenges, including low student participation, limited enthusiasm during learning activities, and the use of learning media that is often less interactive. This study aimed to describe the implementation of Wordwall-based educational game media in motivating students, identify the obstacles encountered by teachers and the strategies used to overcome them, and analyze its implications for both students and teachers in fifth-grade Pancasila Education learning at SD Negeri 4 Nyalian, Klungkung Regency. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and literature review. The research informants consisted of the principal, the fifth-grade teacher, and fifth-grade students. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Wordwall-based educational game media was carried out through the stages of lesson planning, implementation, and evaluation. The use of Wordwall created a more engaging, interactive, and enjoyable learning environment, encouraging students to become more active, enthusiastic, and motivated in participating in learning activities. The challenges encountered included limited supporting facilities, shared use of technological devices, and differences in students’ digital literacy skills. To address these challenges, teachers coordinated the use of facilities, provided guidance and assistance to students, and implemented effective classroom management. Furthermore, the use of Wordwall had positive implications for students’ learning motivation, classroom interaction, and teachers’ instructional innovation.